Discussion on the Management of spatio-temporal Data Security for Intelligent Connected Vehicles - Y. Li; H. Zou; Q. Liao; H. Chen; L. Huang; L. Shi; J. Bai (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The spatio-temporal data of intelligent and connected vehicles (ICVs) represent crucial surveying and mapping data generated by these vehicles. The massive collection, processing, and aggregation of such data pose potential security risks to geographic information security and even national security. This paper analyzes the significance of spatio-temporal data in ICVs and provides extensive application examples. By comparing the current research status in the United States, the European Union, Japan, it elaborates in detail on China's management status and summarizes practical experience in multiple advanced cities within the country for safety management.Incorporating the current domestic processes of spatio-temporal data generation, transmission, and processing, the paper assesses data security risk,network security risk, and system security risk. Furthermore, this paper proposes recommendations on how to establish spatio-temporal data security management system from various levels, including government, enterprises, and society, to effectively address potential and existing security risks.